Influence Product Quality, Prices and Social Media Marketing On Purchasing Decisions Product Gurita Bouquet ( Flower Bouquet ) - Alfiyanti, Annisa Putri; Karamang, Ezra (International Journal of Marketing & Human Resource Research, 2025)
This investigation aims to evaluate the impact of product quality, price, and social media marketing on the purchasing decisions of Gurita Bouquet products in Bandung City. Companies must develop effective marketing strategies to pique consumer interest in the florist industry, characterized by intense competition. A quantitative methodology is implemented in this investigation, which includes 95 participants. This investigation employed A Purposive Sampling approach in conjunction with Non-Probability Sampling. A total of 95 questionnaires were distributed to respondents who are 19 years of age or older and have purchased Gurita Bouquet products to investigate the impact of product quality, price, and social media marketing on their purchasing decisions for Gurita Bouquet products. The questionnaires were successfully collected. The findings indicated that purchasing decisions were significantly influenced by product quality, price, and social media marketing. The r count and Cronbach Alpha values are above the standard, indicating that the validity and reliability tests yield satisfactory results. The t-test, which was employed to test the hypothesis, demonstrates that the three independent variables substantially impact purchasing decisions. The sig value is less than 0.05, and the t count exceeds the t table. The F test demonstrates that the three variables substantially impact purchasing decisions simultaneously. In general, the findings of this investigation indicate that the quality of the product, the pricing, and the use of social media marketing are significant factors in the decision-making process for Gurita Bouquet products